If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8S + 4 + 2S + -2 = 0 Reorder the terms: 4 + -2 + 8S + 2S = 0 Combine like terms: 4 + -2 = 2 2 + 8S + 2S = 0 Combine like terms: 8S + 2S = 10S 2 + 10S = 0 Solving 2 + 10S = 0 Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 10S = 0 + -2 Combine like terms: 2 + -2 = 0 0 + 10S = 0 + -2 10S = 0 + -2 Combine like terms: 0 + -2 = -2 10S = -2 Divide each side by '10'. S = -0.2 Simplifying S = -0.2
| 2y-1y+15=22 | | 4(9-6x)=36 | | 4x^3+x^2+12x+3=0 | | 2=14k | | 49x^2+14xy+y^2=0 | | 4(3x+6)=-12 | | 6(-1x+2)=-60 | | 12+d=112 | | 5x(x+2)=80 | | 3x^5+12x^3= | | 2(1x+1)=14 | | 3x^5-12x^3= | | 4m-7=13 | | 243-(67+92)=84 | | 8x+30=7x+30 | | 36=2x+15 | | P=2x+3y | | -45*(-8)-(-13)= | | -8x-2+7x=-9 | | 13=2x+15 | | -2(2x+4)=-16 | | 2x-21-x+10=-1 | | 3(x+8)=45 | | 7(1+2x)=147 | | -6=11x-5x | | 5x+2(6)=3x(11) | | 15=5-2x | | 6(2x+7)=126 | | -4(-2+5x)=28 | | X^2+4xy+5x=0 | | (-3)/(-10)*0*(-2)= | | -5(7+7x)=-105 |